Medical genetics at a glance - Pritchard, D. J; Korf, Bruce R (Wiley-Blackwell, 2013)
A university textbook that focuses on medical genetics.
At a glance series
Keywords: lékařská genetika; Genetics, Medical; genetika, lékařská genetika